Defense industrial complex for development of the national innovation system - Nguyen Quang Tuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Defense-industrial complex (DIC) refers to the partnership between defense enterprises and institutions of national innovation system for research, development and production of weapon systems, military products and materials. DIC plays an essential role in improving the autonomous capability of national defense industry, contributing to national security and promoting the development of commercial industries and national innovation system. This paper analyses the DIC’s role for different countries, the relationship between DIC and national innovation system; making recommendations for policy development of DIC in Vietnam. Code: 23110601